Is there a hold-up benefit in heterogeneous multiple bank financing? - Christina E. Bannier (Frankfurt School of Finance & Management, 2009)
This paper studies the effects that heterogeneous multiple bank financing has on a firm's risk- and information-policy, particularly with respect to credit renegotiation efficiency. We find that a significant, yet limited, degree of relationship lending enables firms with high asset specificity to credibly signal their desire to abstain from strategic default. This allows the firm's policy to eliminate the risk of inefficient liquidation even in the case of bleak cash-flow expectations. This hold-up benefit comes at a cost, though: firms with low asset specificity cannot always eliminate the risk of coordination failure by their banks.
urn:nbn:de:101:1-2009042200
Keywords: D82; G21; L14; 330